8.2k views
4 votes
Find (g∘g)(−1)for g(x)=4x2+3x−3. (g∘g)(−1)=

1 Answer

3 votes

Given:


g(x)=4x^2+3x-3

We're asked to find the value of:


(g\circ g)(-1)

What we're going to do is to find the value of g(-1) first:


(g\circ g)(-1)=g(g(-1))
\begin{gathered} g(-1)=4(-1)^2+3(-1)-3 \\ g(-1)=4-3-3 \\ g(-1)=-2 \end{gathered}

Now,


g(g(-1))=g(-2)

The value of the composite function equals g(-2):


\begin{gathered} g(-2)=4(-2)^2+3(-2)-3 \\ g(-2)=4(4)-6-3 \\ g(-2)=16-6-3 \\ g(-2)=7 \end{gathered}

Therefore,


(g\circ g)(-1)=7

User Dlani Mendes
by
4.9k points